2020
DOI: 10.1029/2019ja027007
|View full text |Cite
|
Sign up to set email alerts
|

Jovian Auroral Ion Precipitation: X‐Ray Production From Oxygen and Sulfur Precipitation

Abstract: Many attempts have been made to model X‐ray emission from both bremsstrahlung and ion precipitation into Jupiter's polar caps. Electron bremsstrahlung modeling has fallen short of producing the total overall power output observed by Earth‐orbit‐based X‐ray observatories. Heavy ion precipitation was able to reproduce strong X‐ray fluxes, but the proposed incident ion energies were very high ( >1 MeV per nucleon). Now with the Juno spacecraft at Jupiter, there have been many measurements of heavy ion populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 46 publications
(133 reference statements)
2
19
0
Order By: Relevance
“…Cravens et al (1995);Dunn et al (2016); Wibisono et al (2020) also led to conclude that the ions responsible for the X-ray aurora are predominantly from Io's volcanoes. Theoretical and modelling studies agree with those findings and show that precipitating high energy state S and O ions charge exchanging with native neutrals in Jupiter's atmosphere can produce Jupiter's auroral soft X-rays (Cravens et al (1995); Hui et al (2009Hui et al ( , 2010; Ozak et al (2010Ozak et al ( , 2013; Houston et al (2020)). All of this supports our conclusion that the X-ray emissions observed during the dawn storms and injections of Events A and B have their ultimate origin in Io's volcanic activity.…”
Section: Discussionsupporting
confidence: 74%
“…Cravens et al (1995);Dunn et al (2016); Wibisono et al (2020) also led to conclude that the ions responsible for the X-ray aurora are predominantly from Io's volcanoes. Theoretical and modelling studies agree with those findings and show that precipitating high energy state S and O ions charge exchanging with native neutrals in Jupiter's atmosphere can produce Jupiter's auroral soft X-rays (Cravens et al (1995); Hui et al (2009Hui et al ( , 2010; Ozak et al (2010Ozak et al ( , 2013; Houston et al (2020)). All of this supports our conclusion that the X-ray emissions observed during the dawn storms and injections of Events A and B have their ultimate origin in Io's volcanic activity.…”
Section: Discussionsupporting
confidence: 74%
“…When Juno is nearer the polar regions, JEDI will allow us to detect and analyze the MeV ions that we expect to underpin the X‐ray aurora mechanism. Houston et al () start to investigate the MeV polar ions in the context of X‐ray emissions to help use the in situ data to provide a vital contribution on trying to answer the origin of the soft Jovian X‐rays and their corresponding (quasi‐) pulsating driver.…”
Section: Discussionmentioning
confidence: 99%
“…This emission is found to mainly reside in a “hot spot” of emission near the northern and southern poles with a total power of 1 GW to a few GW. Recent work, using the most updated Jovian ion models and in situ data, has found that the very energetic heavy ions (up to approximately few MeV and above in some cases) in this region are responsible for most of the total power output of the X‐rays (Houston et al, ). The X‐ray emissions in this region have been observed to exhibit quasiperiodic pulsations during several intervals (Dunn et al, , ; Elsner et al, ; Gladstone et al, ; Jackman et al, ; Kimura et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These lines are produced when ions collide with atmospheric neutrals and charge exchange to take an electron from a neutral and consequently emit an X-ray photon (Cravens et al, 1995). If the precipitating ions are of a magnetospheric origin, then they will be only singly or doubly charged (e.g., O +,2+ ) and must therefore undergo a series of high energy (>0.5 MeV/u) collisions that strip electrons from them before they are of a sufficiently high charge state (e.g., O 6+,7+ ) to produce the observed X-ray spectral lines (Houston et al, 2018(Houston et al, , 2020. Clark et al (2017) have shown that large potential drops do exist over Jupiter's pole, which may provide at least part of the ion acceleration to produce the observed X-rays.…”
Section: Introductionmentioning
confidence: 99%